THE EMANCIPATORY RIGHTS OF AFRO-BRAZILIANS IN THE SUPREME FEDERAL COURT THE ADPF N. 186/12 AND ADI 3239/18 CASES - da Silva, Rodrigo Umbelino (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
This article aims to present the way in which emancipatory rights are presented in the Federal Supreme Court through two case studies. The construction of the idea of ​​emancipatory rights portrayed in this article was built on the basis of Franz Neumann's theoretical discussion, since for this author, law in the 20th century, depending on the state model and its democratic character, can foster changes in reality. society of a given society. In the second part of the research, we will present the arguments built by the Ministers of the Federal Supreme Court in the light of the debate around the ADPF 186/12 and ADI 3239/18 actions. In general terms, at the end of this work we demonstrate that the law is a fundamental instrument for the consolidation of fundamental rights and the Federal Supreme Court, in addition to exercising an important role of constitutional control, may also contribute to the consolidation of racial quotas policies and to the recognition of the land rights of quilombola populations.
Keywords: Afro-Brazilians. Emancipatory rights . Federal Supreme Court.